[Bullhead buster] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Bullhead buster was used to to cultivate rocky land.
Cataloger's title
Keywords: Sugar machinery -- Trinidad and Tobago; Caroni (1975) Limited